1992
DOI: 10.1038/sc.1992.101
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of seating pressure using FES in patients with spinal cord injury. A preliminary report

Abstract: Reduction of seating pressure using FES in patients with spinal cord injury. A preliminary report. The aim of this study was to investigate the use of functional electrical stimulation (FES) as a means of pressure sore prevention in seated spinal cord injured (SCI) subjects. Nine SCI subjects took part in tests in which electrical stimulation was applied to the quadriceps with the lower legs restrained. Ischial pressures were measured during periods of quiet sitting and FES application. A strain gauged lever a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 2 publications
1
22
0
3
Order By: Relevance
“…Ferguson et al applied electrical stimulation to the quadriceps muscles and found that the greater the knee extension movement, the more significant the decreases in pressure at the ischial tuberosity. 18 A decade later, Bogie and Triolo used implanted neuromuscular stimulation of the gluteal muscles to assist individuals with standing and transfer activities.…”
mentioning
confidence: 99%
“…Ferguson et al applied electrical stimulation to the quadriceps muscles and found that the greater the knee extension movement, the more significant the decreases in pressure at the ischial tuberosity. 18 A decade later, Bogie and Triolo used implanted neuromuscular stimulation of the gluteal muscles to assist individuals with standing and transfer activities.…”
mentioning
confidence: 99%
“…They proposed that these reductions were more appropriate than the redistributions that had been shown by Levine's group with NMES of GM [21]. Their protocol involved a 3 months conditioning program (30 min/day × 5+ days/week) prior to testing, and resulted in average ischial pressure reductions of 3.6 kPa (27 mmHg) and 5.9 kPa (44 mmHg) on the left & right sides respectively (from means of 10.1 kPa (76 mmHg) and 13.2 kPa (99 mmHg) respectively at rest).…”
Section: State Of the Artmentioning
confidence: 99%
“…Flap reconstruction to provide well-vascularized, bulky tissue to cover bony prominences was pioneered by Davis in the 1930s [18]. Since 1970, gluteal flaps have been used widely, as originally described by Ger [21,50]. Although still the best option available, post-operative recurrence rates are as high as 61% within the first year of repair, and vary widely [19,65] (Table 1).…”
Section: Clinical Scope and Outcomesmentioning
confidence: 99%
“…[7][8][9][10][11] Levine et al 8,9 used surface ES in the gluteal muscles of individuals with an SCI and found a changed buttock tissue shape 8 and increased muscle BF. 9 Ferguson et al 7 stimulated the quadriceps muscles and found a decrease in interface pressure as well.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Levine et al 8,9 used surface ES in the gluteal muscles of individuals with an SCI and found a changed buttock tissue shape 8 and increased muscle BF. 9 Ferguson et al 7 stimulated the quadriceps muscles and found a decrease in interface pressure as well. Smit et al 12 found that ES-induced gluteal and hamstring muscle activation reduces IT pressure and, in a 3-h stimulation period with a 1:4 s on-off duty cycle, does not cause muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%